Specific physiological and biomechanical performance in elite, sub-elite and in non-elite male team handball players - Wagner, H.; Fuchs, P. X.; von Duvillard, S. P. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: Team handball is a dynamic sport game that is played professionally in numerous countries. However, knowledge about training and competition is based mostly on practical experience due to limited scientific studies. Consequently, the aims of our study were to compare specific physiological and biomechanical performance in elite, sub-elite and in non-elite male team handball players. METHODS: Thirty-six elite, sub-elite and non-elite male team handball players performed a game based performance test, upper-body and lower-body strength tests, 30m sprint test, counter movement jump test and an incremental treadmill running test. RESULTS: Significant differences (P<0.05) were found for the peak oxygen uptake, heart rate, offense and defense time, jump height and ball velocity during the jump throw in the game based performance test, maximal oxygen uptake in the incremental treadmill running test as well as in maximal leg strength and leg explosive strength in the isometric strength test. CONCLUSIONS: Elite male players have an enhanced specific agility, a better throwing performance, a higher team handball specific oxygen uptake and higher leg strength compared to sub-elite and non-elite players. Based on these results we recommend that training in team handball should focus on game based training methods to improve performance in specific agility, endurance and technique.